IMPROVEMENT OF SPEAKING SKILLS THROUGH SCRIPT COOPERATIVE LEARNING MODEL ON CLASS X STUDENTS OF SMAN 7 GOWA - Kasma F Amin; Nurfathanah Mazhud; Nurwahyuli Nurwahyuli (maktab: Jurnal Pendidikan dan Teknologi, 2022)
Speaking skill is one type of language skill that is very important to be taught to students. The purpose of this research is to improve the speaking skills of the tenth graders of SMAN 1 Gowa using the cooperative script method. This research is a CAR research with Kurt Lewin's model which consists of four stages, namely planning, implementation, observation, and reflection. The results showed that there was an increase in the average score of pre-cycle speaking development scores from 62.15 to 67.51 after the first cycle of action was held. At the end of the second cycle of action, the average obtained by students reached 79.55. This shows an increase of 12.5 points. The specified KKM is 70, in the pre-cycle activities that reach the KKM as many as 5 people or 15%. In the first cycle activities in class X IPA 2 students who reached the KKM were 12 people or 40%. In cycle 2 who reached the KKM as many as 26 people or 98%. Based on these results, it can be concluded that the cooperative script method can improve the speaking skills of the tenth graders of SMAN 7 Gowa on debate material.